2014
DOI: 10.1165/rcmb.2013-0349oc
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Bone Morphogenetic Protein Receptor 2 Is Associated with Abnormal DNA Repair in Pulmonary Arterial Hypertension

Abstract: Occlusive vasculopathy with intimal hyperplasia and plexogenic arteriopathy are severe histopathological changes characteristic of pulmonary arterial hypertension (PAH). Although a phenotypic switch in pulmonary endothelial cells (ECs) has been suggested to play a critical role in the formation of occlusive lesions, the pathobiology of this process is poorly understood. The goal of this study was to identify novel molecular mechanisms associated with EC dysfunction and PAH-associated bone morphogenetic protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 50 publications
4
72
0
2
Order By: Relevance
“…We provide extensive evidences linking the abnormal expression of miR-223 to already known pathophysiological processes in PAH, including HIF-1␣ activation (2, 32), impaired DNA damage signaling (9,19), and PARP-1 overexpression (23), as well as the proliferation/apoptosis imbalance of PAH-PASMC (37). Thus, our study not only demonstrates the importance of miRNAs especially miR-223 in PAH but also, on the basis of our in vivo data, suggests that it might represent a new therapeutic target for human PAH.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We provide extensive evidences linking the abnormal expression of miR-223 to already known pathophysiological processes in PAH, including HIF-1␣ activation (2, 32), impaired DNA damage signaling (9,19), and PARP-1 overexpression (23), as well as the proliferation/apoptosis imbalance of PAH-PASMC (37). Thus, our study not only demonstrates the importance of miRNAs especially miR-223 in PAH but also, on the basis of our in vivo data, suggests that it might represent a new therapeutic target for human PAH.…”
Section: Discussionmentioning
confidence: 99%
“…We and others highlighted the role of DNA damage signaling and PARP-1 activation in PAH lung vascular cells (9,19,23), but the exact mechanism underlying this deregulation remains unknown. In silico analysis using TargetScan 6.2 revealed that PARP-1 is a predicted target of miR-223.…”
Section: Mir-223 Downregulation Promotes Parp-1 Expression In Human Pmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding how aberrant molecular signaling causes DNA damage as an early event that initiates vascular remodeling is the subject of ongoing investigation (18). For example, the inflammatory mediator TNF-α (19), and genetic deficiency of BMPR2 or TopBP1 (20,21) can both promote DNA damage and impair endothelial cell proliferation and survival. Recently, we demonstrated that oxidative stress caused by reoxygenation after hypoxia combined with BMPR2 deficiency induced a mitochondrial DNA deletion, elevated caspase-3/7 activity in PAECs, and impaired reversal of pulmonary hypertension (22).…”
Section: Introductionmentioning
confidence: 99%